Optimization Of Formula SNEDDS Mahogany Seed Oil (Swietenia mahagoni (Linn.)) with Simplex Lattice Design Method - Nurista Dida Ayuningtyas; Agustina Putri Pitarisa S; Silmi Mey Aryani (Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
Mahogany seed oil has antimicrobial, antihypertensive, antidiabetic and anti-inflammatory activities. This activity can be developed in SNEDDS dosage form. SNEDDS can deliver lipophilic drugs to the target side of the drug. SNEDDS has oil components, surfactants, and co-surfactants. In this study, optimization of the SNEDDS formula with the SLD method will be carried out. The oil components tested were oleic acid, VCO and HDI; surfactants namely Cremophor RH40 and Tween 80; and co-surfactant components, namely PEG 400 and propylene glycol. The tests for SNEDDS were transmittance, pH, and emulsification time. The results of the evaluation were analyzed to obtain the optimal formula and determined the loading dose. The next test was to determine the particle size and zeta potential to see the stability of SNEDDS mahogany seed oil. Result : Optimal formula composition obtained oleic acid 1,00 Cremophor RH 40 7,89 and PEG 400 1,11 with desirability value 0,988. Loading dose of mahogany seed oil obtained 800 l with a transmittance value of 99,3 % + 0,44 ; pH 5,06 + 0.63 , and emulsification time 74,04 + 6,05 seconds. SNEDDS mahogany seed oil measuring 17,7 nm + 0,3 with a potential zeta value of -22,67 mV + 0,47. SNEDDS mahogany seed oil obtained belongs to Grade A where SNEDDS quickly forms nanoemulsions in 1 minute, has a clear appearance.